Finite element solution of thermal radiation effect on unsteady MHD flow past a vertical porous plate with variable suction, “This paper has been withdrawn” - Gundagani, Murali; Reddy, MCK; Babu, NVN; Sivaiah, S. (International Journal of Engineering and Technology, 2012)
This paper has been withdrawn.